A new Cyrtodactylus (Squamata: Gekkonidae) from Khanh Hoa Province, southern Vietnam - Schneider, Nicole; Phung, Trung My; Le, Minh Duc; Nguyen, Truong Quang; Ziegler, Thomas (Zootaxa, 2014)
We describe a new species of the genus Cyrtodactylus from southern Vietnam, based on morphological and molecular datasets. Cyrtodactylus cucdongensis sp. nov. is described on the basis of seven specimens collected from Cuc Dong Cape, Khanh Hoa Province. The new species can be distinguished from the remaining bent-toed geckos by a combination of the following characters: maximum SVL 65.9 mm; 16–19 dorsal tubercle rows; 41–44 ventral scales at midbody; 5 or 6 precloacal pores in males, 4–6 pitted precloacal scales in females; no femoral pores; 6–13 enlarged precloacal scales; 5–9 enlarged femoral scales; no transversally enlarged subcaudals; dorsal pattern consisting of irregular dark bands. This is the 33rd species of Cyrtodactylus known from Vietnam.